The future impact of oil volatility on commodity prices - Arreguin, Juan Carlos; Kakooza, Evelyne; Somogyiová, Zuzana (Univerzita Pardubice, 2010)
The aim of this research was to compare two methods used in terms of oil volatility and its effects on the development of different commodities. We tried to find out if there is any positive or negative relationship between price movements and if the volatility prices of oil affect the volatility prices of silver, copper and aluminium. For the purpose of this study we used GARCH and VAR models. When examining oil volatility by VAR model, we used the Granger-Causality test to find causality between commodities. And at the end of this research we examined by the impulse responses and the variance decompositions whether changes in the value of a given commodity have a positive or negative effect on other commodities in the system, or how long it would take for the effect of that commodity to work through the system.
Keywords: volatility; VAR; GARCH; commodity; oil